1998
DOI: 10.1007/s005350050123
|View full text |Cite
|
Sign up to set email alerts
|

Clinical application of hepatitis C virus core protein in early diagnosis of acute hepatitis C

Abstract: A fluorescence enzyme immunoassay (FEIA) for the quantitative measurement of hepatitis C virus (HCV) core protein has recently been developed. In this study, we studied the clinical usefulness of this measurement in patients with acute hepatitis C. Eighteen patients with post-transfusion acute hepatitis C were enrolled in the study; 5 patients showed resolution of hepatitis with disappearance of HCV viremia, while the remaining 13 patients did not. A second generation HCV antibody, HCV RNA, and HCV core protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 21 publications
2
12
0
Order By: Relevance
“…In this study, HCV core antigen was detected in the vast majority of preseroconversion specimens containing HCV RNA. These results correlate with previous reports of the presence of HCV antigen in RNA–positive specimens from patients with acute and chronic HCV infection [9, 10, 11, 12]and support a recent report of the presence of HCV antigen during the early, RNA–positive phase of anti–HCV seroconversion [13]. The results reported here also indicate that HCV core antigen appears substantially earlier than HCV antibody during the early phase of HCV infection and contemporaneously with HCV RNA in most seroconversion cases.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In this study, HCV core antigen was detected in the vast majority of preseroconversion specimens containing HCV RNA. These results correlate with previous reports of the presence of HCV antigen in RNA–positive specimens from patients with acute and chronic HCV infection [9, 10, 11, 12]and support a recent report of the presence of HCV antigen during the early, RNA–positive phase of anti–HCV seroconversion [13]. The results reported here also indicate that HCV core antigen appears substantially earlier than HCV antibody during the early phase of HCV infection and contemporaneously with HCV RNA in most seroconversion cases.…”
Section: Discussionsupporting
confidence: 82%
“…Recent reports have suggested that it is possible to identify HCV core antigen in sera derived from individuals infected with HCV that contain HCV RNA [9, 10, 11, 12, 13]. These studies have generally been carried out using antibody–positive specimens derived from chronic HCV infection and have utilized specimen pretreatment in order to detect HCV core antigen.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, HBsAg cannot be used as virus load marker. Measurement of the HCV core antigen after specimen pretreatment has been reported useful for the diagnosis and monitoring of hepatitis C (13,15,19,21,28,30). We previously developed a highly sensitive EIA for HCV core antigen (1,29).…”
Section: Discussionmentioning
confidence: 99%
“…Measurement of the HCV core antigen after specimen pretreatment has been reported as useful for diagnosing and monitoring hepatitis C (12,15,18,26). A highly sensitive EIA was previously developed for the HCV core antigen (1,2,27) in which the HCV core antigen was released from the virion by SDS pretreatment prior to EIA detection.…”
Section: Discussionmentioning
confidence: 99%